High Prevalence of Multimorbidity and Polypharmacy in Elderly Patients With Chronic Pain Receiving Home Care are Associated With Multiple Medication-Related Problems - Schneider, Juliana; Algharably, Engi Abd Elhady; Budnick, Andrea; Wenzel, Arlett; Dräger, Dagmar; Kreutz, Reinhold (Frontiers in Pharmacology, 2021)
Aim: To measure the extent of polypharmacy, multimorbidity and potential medication-related problems in elderly patients with chronic pain receiving home care. Methods: Data of 355 patients aged ≥ 65 years affected by chronic pain in home care who were enrolled in the ACHE study in Berlin, Germany, were analyzed. History of chronic diseases, diagnoses, medications including self-medication were collected for all patients. Multimorbidity was defined as the presence of ≥ 2 chronic conditions and levels were classified by the Charlson-Comorbidity-Index. Polypharmacy was defined as the concomitant intake of ≥ 5 medications. Potentially clinically relevant drug interactions were identified and evaluated; underuse of potentially useful medications as well as overprescription were also assessed. Results: More than half of the patients (55.4 %) had moderate to severe comorbidity levels. The median number of prescribed drugs was 9 (range 0 - 25) and polypharmacy was detected in 89.5% of the patients. Almost half of them (49.3 %) were affected by excessive polypharmacy (≥ 10 prescribed drugs). Polypharmacy and excessive polypharmacy occurred at all levels of comorbidity. We detected 184 potentially relevant drug interactions in 120/353 (34.0 %) patients and rated 57 (31.0 %) of them as severe. Underprescription of oral anticoagulants was detected in 32.3 % of patients with atrial fibrillation whereas potential overprescription of loop diuretics was observed in 15.5 % of patients. Conclusions: Polypharmacy and multimorbidity are highly prevalent in elderly outpatients with chronic pain receiving home care. Medication-related problems that could impair safety of drug treatment in this population are resulting from potentially relevant drug interactions, overprescribing as well as underuse.